Socialization of Safe and Legal Investment in the Digital Era to the Babat Village Community - Arisandra, Martha Laila; Azizi, Khoirun Agil; Taqiyyuddin, Mochammad; Nawawi, Muhammad Imam; Nisma, Anggi (Society : Jurnal Pengabdian Masyarakat, 2025)
The digital era has brought significant changes to the world of investment, offering easier and wider access for the public. However, the increase in digital investment has also been followed by the rise in illegal investments that are detrimental to the public. This socialization aims to improve the public's digital financial literacy, provide an understanding of safe and legal investments, and raise awareness of the risks of illegal investments. Through interactive lecture methods, group discussions, and case studies, this socialization succeeded in increasing participants' understanding of the characteristics of illegal investments, legal investment platforms, and how to protect themselves from online investment fraud. The evaluation results showed a significant increase in participants' digital financial literacy after participating in the socialization. The implications of this activity are increased public participation in legal digital investments and protection from losses due to fraudulent investments.